The rise of Shimao 2800–1300 BC in the North Loess Plateau, China: an exploration of the climate, demographic, economic, material culture influences - Fung, YT (2021)

(untitled)
The recognition in 2011 of the extraordinary Shimao site (ca. 2300–1800 cal. BC) in the North Loess Plateau as late Neolithic China’s largest stone fortification, has overturned our understanding of the development of complex societies in northern China. The 400-hectare stone fortification of Shimao lies at the heart of the climate-sensitive region (hereafter the Shimao region), which located at the junction of modern-day south-central Inner Mongolia, northern Shaanxi and northern Shanxi, featuring numerous stone fortifications during the period ca. 2800–1300 cal. BC. The settlements in this region have the unusual combinations of herd animals, millet, ceramic tripods, and high-valued jade and bronze artefacts, suggesting a development in wealth and social economy. The central question addressed in this thesis is how and why Shimao, along with the surrounding settlements, flourished in the south sector of the region.